A rare case of culture-negative infective endocarditis following cataract surgery - Gayashani K. Jayasinghe; Logeswaran Dinusha; Udara S. Perera; Indrakumar Jegarajah (Journal of International Medical Research)
A 70-year-old man developed intermittent fever with chills, severe anorexia, generalized weakness, and mild exertional difficulty in breathing following posterior chamber intraocular lens replacement surgery for a mature white cataract in the left eye. Laboratory tests revealed persistent negative blood cultures, normocytic and normochromic anemia, neutrophilia, and elevated inflammatory markers despite multiple courses of antibiotics. All other investigations conducted to identify the cause of prolonged fever, including transthoracic echocardiography, were negative. However, transesophageal echocardiography detected an aortic valve vegetation. The patient had no history of valvular disease or any predisposing condition for infective endocarditis. The bacteremia was strongly suspected to have resulted from cataract surgery, although no obvious signs of eye infection were observed during the postoperative period. The patient was treated with empirical antibiotics, including vancomycin and ceftriaxone, which led to significant improvement. Because infective endocarditis remains a significant public health concern with increasing incidence rates, we present this unusual case of culture-negative infective endocarditis following cataract surgery, highlighting the diagnostic and therapeutic challenges encountered.